Kontribusi Minat Belajar, Kemandirian Belajar, Dan Kreativitas Belajar Terhadap Keterampilan Literasi Membaca Siswa - Hendra, I Made Hendra Sukmayasa; Sudiana, I Nyoman (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Sarjanawiyata Tamansiswa, 2024)
The aim of this research is to determine the contribution of learning interest, learning independence, and learning creativity to the reading literacy skills of class IV students at SD Cluster III, Buleleng District. This research is an ex-post facto research with a Correlation Study Survey design. The population of this study was all students in class IV of SD Cluster III, Buleleng District, totaling 394 students. Meanwhile, the sample for this research was 196. The independent variables in this research were students' interest in learning, learning independence, and students' learning creativity, while the dependent variable was students' reading literacy skills. Data on learning interest and learning independence were collected using a questionnaire. Data on students' learning creativity was collected using tests, while data on students' reading literacy skills was collected by studying documents owned by teachers at school. The data analysis methods used in this research are quantitative descriptive analysis methods, simple regression analysis, multiple regression and partial correlation. Based on the research that has been conducted, it is concluded that: 1) there is a significant contribution of interest in learning to students' reading literacy skills with a contribution of 42.1% and an effective contribution of 20.7%. 2) there is a significant contribution of independent learning to students' reading literacy skills with a contribution of 44.4% and an effective contribution of 18.5%. 3) there is a significant contribution of learning creativity to students' reading literacy skills with a contribution of 44.1% and an effective contribution of 17%. And 4) simultaneously, there is a significant contribution of learning interest, learning independence, and learning creativity to students' reading literacy skills with a contribution of 56.2%.